Volume 1: Fora, Parts a and B 2002
DOI: 10.1115/fedsm2002-31017
|View full text |Cite
|
Sign up to set email alerts
|

A Description of the Pressure Swirl Atomizer Internal Flow

Abstract: The context of the present work is an investigation of the influence of geometry on the structure of the pressure swirl atomizer internal flow. Vizualisations and measurements techniques (LDA and PIV) are used on a large-scale pressure swirl atomizer. The behaviour of inlets jets and the development of the swirling flow are studied. Measurements of the aircore/liquid interface instabilities revealed the fundamental influence of inlet slots and exit orifice. Finally, a comparison between experimental results an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
4
11
0
Order By: Relevance
“…The higher peak appears to be the result of the rotating double helix wave. These results concur with those of Donjat et al [18] who also found two fundamental spectral frequencies and also mention the presence of capillary waves, in addition to the helical and air core precession, based on numerical results and laser spectrum analysis. Figure 6 indicates that the highest magnitudes of the velocity components are found near the air core, with the second highest values in the near wall region.…”
Section: Small Amplitude Capillary Wavessupporting
confidence: 92%
“…The higher peak appears to be the result of the rotating double helix wave. These results concur with those of Donjat et al [18] who also found two fundamental spectral frequencies and also mention the presence of capillary waves, in addition to the helical and air core precession, based on numerical results and laser spectrum analysis. Figure 6 indicates that the highest magnitudes of the velocity components are found near the air core, with the second highest values in the near wall region.…”
Section: Small Amplitude Capillary Wavessupporting
confidence: 92%
“…Experimentally, such helical structure has been observed by several authors, including Kim et al (2009), Donjat et al (2002) and Cooper and Yule (2001), while the phenomenon has also been demonstrated in CFD simulations by Dash et al (2001). The variation of the air core may induce large fluctuations of the film thickness and affect the subsequent atomization process (Amini, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…These features of the flow are clearly amenable to a boundary layer type of analysis. However, recirculation in the bulk of the atomizer chamber, which is a prominent feature displayed by experimental visualizations (Binnie et al 1957;Wang et al 1999;Donjat et al 2003) and numerical computations (Jeng et al 1998;Yule & Chinn 2000;Nouri-Borujerdi & Kebriaee 2012) for moderate to small values of the atomizer constant, can hardly be accounted for using a boundary layer approximation. The size of the recirculation region and the direction of circulation of the liquid depend on the inlet conditions.…”
Section: Viscous Effectsmentioning
confidence: 99%
“…Experiments with various geometrical configurations, liquid properties and injection pressures and/or flow rates (Dombrowski & Hasson 1969;Rizk & Lefebvre 1985;Horvay & Leuckel 1986;Suyari & Lefebvre 1986;Kim et al 2009) have clarified the effects of these parameters on the characteristics of the atomizer, allowing one to assess and to extend the predictions of irrotational theories (Lefebvre 1989). Large-scale models made of transparent materials have allowed optical access and measurements at increased spatial resolution with laser Doppler velocimetry, particle image velocimetry, laser-induced fluorescence and high-speed video techniques (Horvay & Leuckel 1986;Holtzclaw et al 1997;Wang et al 1999;Donjat et al 2003). These experiments have revealed the complexity of the flow in the chamber, which includes regions of very different axial and azimuthal velocities, recirculation, non-steadiness, lack of axisymmetry and waves propagating on the liquid-air interface.…”
Section: Introductionmentioning
confidence: 99%